Corneal Endothelial Cell Loss Following Cataract Surgery in Patients with Type 2 Diabetes Mellitus: A Comprehensive Review - Mădălina-Casiana Salavat; Mihnea Munteanu; Vlad Chercotă; Adina Iuliana Ardelean; Amanda Schuldez; Valentin Dinu; Ovidiu Borugă (Biomedicines, 2025)
Cataract surgery, while commonly considered a routine, highly effective, and generally low-risk ophthalmic procedure, has been associated with corneal endothelial cell loss (ECL), a phenomenon particularly pronounced in patients with type 2 diabetes mellitus (DM2). This increased susceptibility in diabetic patients is often attributed to pre-existing corneal abnormalities, including compromised structural integrity and reduced endothelial cell density. Additionally, metabolic stress factors inherent to diabetes, such as chronic hyperglycemia and associated oxidative stress, further exacerbate endothelial vulnerability. Consequently, diabetic patients may experience significantly greater endothelial cell loss during and after cataract surgery, necessitating targeted surgical strategies and careful perioperative management to preserve corneal health and visual outcomes. This paper aims to conduct an extensive and detailed review of the existing scientific literature to thoroughly investigate the relationship between ECL and cataract surgery in patients diagnosed with DM2. This study conducts a critical evaluation to elucidate the mechanisms contributing to high endothelial vulnerability in individuals with diabetes. It systematically compares the rates of ECL observed in diabetic and non-diabetic populations undergoing cataract surgery, examines molecular alterations following the procedure in patients with and without DM2, identifies key risk factors influencing surgical outcomes, evaluates the impact of various surgical techniques, discusses preventative measures, and examines the long-term consequences of ECL in this specific population. Furthermore, this review analyzes the existing research to identify gaps in knowledge and suggest potential directions for future investigations.